Tehnologije plemenitenja: navodila za vaje - Fakin, Darinka; Ojstršek, Alenka (University of Maribor Press, 2019)
Finishing Technologies: Instructions for Exercises. Textile finishing technologies represent a broad and technologically demanding field of work of the textile industry. Textile finishing include a range of operations and processes that provide better look and improved feel, and also increase the applicable and care properties of final textile products. The finishing processes are carried out on different types of textile material (cellulose, protein and synthetic) as well as on various forms of textile material (fibres, yarns, threads, knitted fabrics, woven and non-woven textiles, ready made products). Exercises are prepared in such a way that students, during each exercise, get to know about individual type of material in diverse forms, such as fabrics, yarns or fibres, and about individual process of pre-treatment, dyeing and finishing. The exercises also include standardized analytical methods of quality parameters, which serve to determine the performance of individual finishing process. At the beginning of each exercise, the theoretical background of materials’ finishing are presented briefly, and followed by presentation of their technological realization and laboratory device, on which certain procedure is accomplished.